Upaya Pencegahan Bullying pada Anak Usia Dini melalui Seminar Parenting pada Wali Murid TK Dewi Sartika: Bullying Prevention Efforts in Early Childhood through Parenting Seminar for Dewi Sartika Kindergarten Guardians - Zulfiyah, Farhatun; Agustin, Atika Dwi; Damayanti, Alvina; Solehah, Sevia Imroatus; Azaz, Ikhlasul (JURNAL TILA ( Tarbiyah Islamiyah Lil Athfaal ), 2024)
Bullying cases in early childhood are serious problems that can have a negative impact on children's psychological, social, and academic development. Prevention efforts are important, one of which is through parenting seminars involving parents and teachers. This article aims to analyze the effectiveness of parenting seminars held at Dewi Sartika Kindergarten as a preventive measure against bullying. The method used was the delivery of material with a lecture model and a question and answer session after the seminar to determine parents' understanding of the dangers of bullying and prevention strategies. The results of this activity indicate that parenting seminars function effectively in educating parents about bullying and their role in preventing it. This parenting seminar provides insight to parents about the importance of empathy, social skills, and cooperation with schools to create a safe environment for children. These findings indicate that parenting seminars can be an effective step in reducing the risk of bullying from an early age.